Benefit-cost analysis of forest carbon for landowners: An illustration based on a southern pine plantation - Mei, Bin; Clutter, Michael L. (Frontiers in Forests and Global Change, 2022)
Using a hypothetic southern pine plantation in the state of Georgia of the United States, a benefit-cost analysis of forest carbon is conducted for landowners in the voluntary carbon market. With carbon values being defined by the marginal forest growth, it is found that the inclusion of carbon into the objective function usually leads to longer rotations and higher total profits. In our baseline analysis, the rotation age increases by four years when both timber and carbon are considered. Thus, landowners can benefit from voluntary carbon trading and additional carbon can be fixed in the forests. Landowners’ decision on forest carbon is most sensitive to the discount rate and timber and carbon prices. When the discount rate is higher, future cash flows become less valuable and the optimal rotation shortens. When timber prices exceed carbon price by a large margin, timber value dominates carbon value and the optimal carbon rotation approaches the Faustmann rotation. Therefore, with a higher discount rate and higher timber prices, voluntary carbon trading will result in less carbon additionality. Finally, when the economic uncertainty is incorporated into the decision making, the results tend to be sustained albeit carbon additionality is slightly reduced.